Analysis of Students' Critical Thinking Ability in Solving Mathematical Problems Assisted by Ethnomathematics Based on Adversity Quotient - Yunia Parawansa; Kamid Kamid; Maison Maison (MASI Mandiri Edukasi, 2026)
This study aims to examine critical thinking ability in mathematical problem-solving using ethnomathematics, based on the Adversity Quotient of class IX A MTsN 6 Kerinci Regency. Subjects were selected purposively, comprising 6 students. Data collection techniques included ARP questionnaires, ethnomathematics-assisted critical thinking ability tests, and interviews. The results showed that students' critical thinking ability in solving mathematical problems assisted by ethnomathematics varied across AQ categories. Students with high AQ (Climbers) met most critical thinking ability indicators. They demonstrated high critical thinking ability, while students with moderate AQ (Campers) showed varied fulfillment of indicators at a moderate level, and students with low AQ (Quitters) showed limitations in fulfilling these indicators. Thus, students with high and moderate AQ have superior critical thinking abilities compared to students with low AQ.